Distribution of Rhizopheric actinomycetes on Karst Ecosystem of Gorontalo, Indonesia - Ledy Mutmainah Y Syahril; Wirnangsi D Uno; Abubakar Sidik Katili; Yuliana Retnowati (Microbiology Indonesia, 2023)
Karst ecosystem is one type of extreme marginal soil with low chemical, physical and biological fertility. Karst soil is characterized by high calcium (Ca) content, which can affect the availability of essential elements for plants. Actinomycetes are the pioneers of phosphor-poor soil and are distributed on various types of soil, including Karst soil. Distribution, abundance, and diversity of actinomycetes on plant rhizosphere are strongly influenced by soil physicochemical characteristics. The objective of this study was to obtain the actinomycetes and to determine the abundance and distribution in the rhizosphere of various types of plants in the karst ecosystems of Gorontalo. The soil sampling was conducted on the plant's rhizosphere on Bilato, Karang Putih, and Biluhu Karst Hill of Gorontalo based on the purposive sampling method. The physicochemical analysis included humidity, temperature, and soil acidity. The results showed that actinomycetes were found on various plant rhizospheres with an abundance of about 3x102 to 1x104 CFUmL-1. There were five actinomycetes isolated successfully on the plant rhizosphere.The AB-01 isolate was specifically found on Ficus sp. and Scizium sp, the ABT-01 isolates were just distributed on Plumeria abusta, Leucaena leocepala, and Monrngaceae, whereas AKP-01, AKP-02, and AB- 02 were distributed on almost of plant rhizosphere.